Work Performance Influence on Employee Motivation and Business Productivity in the Accommodation Industry of Ilocos Norte, Philippines - Orpia, Cherie B. (Technium Social Sciences Journal, 2022)
Employees are vital in delivering the products and services of the accommodation industry businesses in Ilocos Norte. The study aimed to analyze the influence of the work motivation of Ilocos Norte employees on their motivation and business productivity. Survey questionnaires were given to 401 employees. The survey inquired level of extrinsic and intrinsic types of work motivation types, level of work performance, and level of impact on business productivity and their interactions. This study used a descriptive-correlational design to interpret the variables' relationships. Multiple linear regression was used to find out predictors that influence work motivation. The result showed workers overall have high and very high levels of extrinsic and intrinsic work motivation, respectively. The level of employee work performance and the level of impact of employee's work performance on business productivity is high. The level of employee work performance is significantly influenced by the level of work motivation of the employees.